Information technology in business principles, practices, and opportunities - Senn, James A (Prentice Hall, 1998)
This second edition focuses on the way Information Technology is transforming the way people do business and how IT impacts their personal lives. The book's emphasis is on the way information technology is used and applied for problem-solving, the new and emerging technologies as they are being implemented in real organizations, applications to personal and professional practice, and the challenges and opportunities of IT in international business situations. For people interested in computers, computer literacy, information systems, or information technology.